Advancements in computational thinking research in science education: a bibliometric analysis of reputable international journals (2014-2024) - Monika Handayani; Bevo Wahono; Rif'at Shafwatul Anam (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This research investigates the development of Computational Thinking (CT) studies in science education by examining selected science journals. It focuses on 1) the distribution of CT research, 2) the proportion of CT-related articles, 3) research methods, 4) authors and citations, 5) education levels, and 6) scientific disciplines and topics. Despite limited systematic literature reviews on CT, its importance in science education is evident as it fosters critical thinking and problem-solving skills. This bibliometric review uses Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to analyze 13 articles from five reputable international journals: Journal of Science Education (IJSE), International Journal of Science and Mathematics Education (IJMA), Journal of Research in Science Teaching (JRST), Science Education (SE), and Research in Science Education (RISE). Findings show that CT research began to develop in 2019. The mixed method is the most widely used in CT research (40%), with JRST publishing the most CT articles (70%). Citations for CT articles are not yet significant, with the highest being 119. Research at the elementary level needs more attention, as many studies focus on secondary schools. CT STEM is the most focused topic in these journals. Other findings are discussed in detail.